2015
DOI: 10.1111/jgs.13298
|View full text |Cite
|
Sign up to set email alerts
|

Total and Differential White Blood Cell Counts in Late Life Predict 8‐Year Incident Stroke: The Honolulu Heart Program

Abstract: Background/Objectives Previous studies have found that higher white blood cell count is associated with incident stroke. However, there are inconsistent results in the elderly and only a few studies have included differential white blood cell counts or Asian populations. We studied the association between total and differential white blood cell counts and incident stroke in an older Asian population. Design Prospective population-based study with 8 years of follow-up. Setting The Honolulu Heart Program, Oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
6
18
1
Order By: Relevance
“…A recent UK large cohort study did not find any association of eosinophils or lymphocytes with stroke or CHD 40 . Our results for stroke are concordant with the literature 41 , 42 as neutrophils were the only component of the WBC count associated with stroke but we did not detect a significant association between neutrophils and CHD. When adjusting for known CVD risk factors, the association between the neutrophil and risk of stroke disappeared, indicating that the effect of neutrophils is not independent from those CVD risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…A recent UK large cohort study did not find any association of eosinophils or lymphocytes with stroke or CHD 40 . Our results for stroke are concordant with the literature 41 , 42 as neutrophils were the only component of the WBC count associated with stroke but we did not detect a significant association between neutrophils and CHD. When adjusting for known CVD risk factors, the association between the neutrophil and risk of stroke disappeared, indicating that the effect of neutrophils is not independent from those CVD risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…However, inconclusive associations were found in hemorrhagic stroke. 9 , 10 , 31 , 44 In concordant with this study, the CKB study showed that higher systemic inflammation measured by CRP was positively associated with the risk of hemorrhagic stroke, 44 while other prospective studies did not find the association between WBC and the incident of hemorrhagic stroke. A possible explanation was that the sample size in previous studies was insufficient to examine the relationships with the risk for hemorrhagic stroke owning to its relatively low incidence.…”
Section: Discussionsupporting
confidence: 84%
“…Monocyte count also emerges to be an independent risk factor for atherosclerotic diseases. However, some epidemiologic and prospective cohort studies indicated that monocytosis was not associated with CHD [49], cardiovascular death [50] or stroke [51]. Moreover, increased circulating monocyte count was correlated with good coronary collateral growth in patients with severely stenotic CAD [52] and with diabetes [53].…”
Section: Resultsmentioning
confidence: 99%